The Young were not Spared: What Death Certificates Reveal about Non-Covid Excess Deaths - Casey B. Mulligan PhD; Robert D. Arnott BS (SAGE Publishing, 2022)
From April 2020 through at least the end of 2021, Americans died from non-Covid causes at an average annual rate of 97 000 in excess of previous trends. Hypertension and heart disease deaths combined were elevated 32 000. Diabetes or obesity, drug-induced causes, and alcohol-induced causes were each elevated 12 000 to 15 000 above previous (upward) trends. Drug deaths especially followed an alarming trend, only to significantly exceed it during the pandemic to reach 108 000 for calendar year 2021. Homicide and motor-vehicle fatalities combined were elevated almost 10 000. Various other causes combined to add 18 000. While Covid deaths overwhelmingly afflict senior citizens, absolute numbers of non-Covid excess deaths are similar for each of the 18 to 44, 45 to 64, and over-65 age groups, with essentially no aggregate excess deaths of children. Mortality from all causes during the pandemic was elevated 26% for working-age adults (18-64), as compared to 18% for the elderly. Other data on drug addictions, non-fatal shootings, weight gain, and cancer screenings point to a historic, yet largely unacknowledged, health emergency.